Modelamiento a escala de poro del transporte de modificadores de humectabilidad (2016)
The purpose of this work is to model and simulate the transport of wettability modifiers in heterogeneous porous media at the pore scale and their impact on multiphase flow properties (i.e. contact angle, relative permeability curves, capillary pressure), in order to scale-up and quantify the effect of wettability modifiers injection on the recovery factor at the macroscale. The multiphase RK Lattice-Boltzmann method for multi-phase flow was used to solve the Navier-Stokes and transport equations at the pore scale in 2D. Contact angle, surface and interfacial tension inherent to these systems are affected by the local chemical concentration, which alters the wettability of the system. Several simulations were carried out to adjust LBM parameters with before and after treatment experimental data. Then, the impact of wettability modifiers injection was predicted using a macroscopic model. Flow properties such as relative permeability curves and capillary pressure were computed for 2D Micro-CT porous media samples, and used as input data in a macroscopic model. The effectiveness of the treatment was found to be a function of the morphology of the system due to its heterogeneities. Thus, not only is the recovery factor dependent on the local concentration of the chemical injected into the porous media, but also on the complex geometry of the system and phase distribution within the pores. Moreover, relationships between chemical concentration and reservoir properties such as residual oil saturation and recovery factor were computed for a wide range of permeability-porosity values for a certain chemical causing wettability alteration. Several models have been developed at the macroscopic scale for designing and predicting the behavior of wettability modifiers injected into the bearing formations. However, the interactions between fluids and reservoir rocks are only deductible at the mesoscale and have direct and emphatic effect on the recovery factor. Therefore, the development of pore scale models becomes the state-of-the-art of the optimization and design of chemical EOR processes.